FISH: A thermal neutron imaging station at HOR Delft. (August 2018) - Zhou, Zhou; Plomp, Jeroen; van Eijck, Lambert; Vontobel, Peter; Harti, Ralph P.; Lehmann, Eberhard; Pappas, Catherine
Abstract: We report on the development of a thermal neutron imaging station FISH at the nuclear research reactor HOR, Delft University of Technology. FISH will serve as a unique new imaging facility within The Netherlands and also within at least 400 km radius, for national and international users from science and industry. This paper gives an overview on the characteristics and performance of the beamline and instrument, as determined in a collaboration with the Paul Scherrer Institut in Switzerland. Highlights: FISH, a thermal neutron imaging station, has been developed at HOR, Delft University of Technology, The Netherlands. This work gives an overview of the characteristics and performance of the beamline and instrument. We are collaborating with internal and external partners to extend the range of experiments and applications of FISH.